PENGARUH ATRIBUT PRODUK, CITRA MEREK DAN KELOMPOK ACUAN TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE SAMSUNG BERBASIS ANDROID DI PONTIANAK (STUDI PADA MAHASISWA DI PONTIANAK) - B31112026, DENNY RUSPANDI (Jurnal Manajemen Update, 2016)
The advancement of information and communication technology has been experiencing a great change along with the era development. Nowadays the communication tools have been converted. We used to use the mobile phone as a means of long distance communication. In the present day, the mobile phone is not only used as a tool of communication, yet it can also be used as a tool to find information. The aims of the study were to seek out: the effect of product attribute, brand image and reference group on Samsung mobile phone android based buying decision. This study employed causal research design. The population of the study was Samsung android users in Pontianak. Purposive sampling technique was employed to select the participants. There were 100 Samsung Galaxcy Grand Series android users included as the participants of the sample; all the participants were domiciled in Pontianak when the data was collected. Multiple regression analysis was employed to analyze the data by testing the validity, reliability and classical assumption at prior. The result of the study revealed that the three variables, in this case product attribute, brand image, and reference group positively and significantly influenced Samsung mobile phone android based buying decision. The reference group dominantly influenced purchase decision. The R2 value was 0,764 which means that 76.40 % of the buying decision were affected by product atribute, brand image and refference group, whilst the rest 23.60 % were affected by other variables which were not included in this study. Keywords : product attribute, brand image, reference group, buying decision.